Effects of urbanization on stream benthic invertebrate communities in Central Amazon - Martins, Renato Tavares; Couceiro, Sheyla R.M.; Melo, Adriano Sanches; Moreira, Marcelo P.; Hamada, Neusa (Ecological Indicators, 2017)
Urbanization and its physical and chemical effects on aquatic environments influence invertebrate communities negatively. Yet, it is not clear how urbanization affects inter-annual variation of invertebrate assemblages in streams. We 1) evaluated urbanization effects on the ecological conditions (biotic and abiotic) of streams in Manaus and 2) analyzed invertebrate community variation over time (between 2003 and 2010). Data on abiotic variables and invertebrates from 2003 were obtained from a previous study. In 2010 we sampled abiotic variables and invertebrate communities in the same low-order urban streams sampled in 2003 (n = 40). We recorded high values of total nitrogen, total phosphorous, deforestation, total impervious area (TIA), water temperature, pH, and electrical conductivity in the most urbanized streams, as compared to the least-impacted ones. In contrast, the least-impacted streams had high dissolved oxygen concentrations. Water quality was poorer in 2010 than in 2003: oxygen concentration was lower and total nitrogen, total phosphorous, deforestation, and TIA significantly higher in 2010. We recorded higher inter-annual variation of abiotic variables in the most-impacted streams as compared to the least-impacted streams. EPT (%, Ephemeroptera, Plecoptera, and Trichoptera) and richness metrics decreased with urbanization. On the other hand, % OP (percent of Oligochaeta and Psychodidae) increased with urbanization. Observed and EPT richness and% OP increased between 2003 and 2010. On the other hand, rarefied richness decreased between years. Increases of observed and EPT richness between 2003 and 2010 were related to low inter-annual variability in streams conditions; however, differences of% OP and rarefied richness were not related to inter-annual variability in environmental conditions. The degree of urbanization did not explain the magnitude of the within-stream difference of invertebrate communities between 2003 and 2010. The increased effects of urbanization represented by the abiotic variables sampled and the reduction of invertebrate richness and increased dominance of tolerant taxa indicate that public policy is not enough to protect or mitigate human impacts on the urban water systems under study. © 2016 Elsevier Ltd
Keywords: Aquatic Organisms; Biochemical Oxygen Demand; Deforestation; Dissolved Oxygen; Nitrogen; Phosphorus; Water Quality; Abiotic Variables; Aquatic Insects; Benthic Invertebrate Community; Dissolved Oxygen Concentrations; Environmental Conditions; Interannual Variation; Invertebrate Assemblages; Urbanization; Rivers; Abiotic Factor; Annual Variation; Benthos; Community Composition; Dissolved Oxygen; Dominance; Electrical Conductivity; Environmental Conditions; Freshwater Environment; Species Richness; Urbanization; Water Quality; Amazonas; Manaus; Ephemeroptera; Hexapoda; Invertebrata; Plecoptera; Psychodidae; Trichoptera